A ANALISIS PENERAPAN SERTA PELAPORAN CSR STRATEGIK DAN NON-STRATEGIK DALAM PERUSAHAAN EKSPOR BERKELANJUTAN - Izzah, Habibatul (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This research aims to describe andanalyze the implementation and reporting of Corporate Social Responsibility (CSR)implementation and reporting on strategic and non-strategic basis in sustainable product exporting companies.exporting company. The study was conducted at PT Mitratani Dua Tujuh, using a qualitative method with a descriptive approach.qualitative method with a descriptive approach. Data was collected through observation,interviews, and documentation. Research resultsshowed that the company implemented 19 CSR activities, consisting of 63% strategic activities that focus on economic, environmental, and social aspects, as well as 37% non-strategic activities that only cover economic and social aspectswithout involving environmental aspects. Since 2023, the CSR report is presentedin the form of a standalone Sustainability Report based on GRI standards, covering economic aspects (e.g.GRI standards, covering economic (GRI 200), environmental (GRI 300), and social (GRI 400) aspects.(GRI 400). However, the report does not identify strategic and non-strategic CSR activitiesstrategic and non-strategic CSR activities explicitly. Previously, CSR reports were preparedas part of the confidential monthly management report. ResearchThis research provides insight into the implementation of CSR as part of the company's sustainability strategy.